'Storying the self': Autobiography as pedagogy in undergraduate creative writing teaching. (1st April 2019) - Moriarty, Jess; Adamson, Ross
The telling and sharing of stories is synonymous with what it is to be human. The narrative threads reaching back through our personal histories can help us to make sense of who we are in the present and we already use these stories anecdotally, at school, on dates, over coffee, in the local, to make connections with people and our social worlds. At an academic level, storytelling that engenders meaning making is becoming legitimized as branch of qualitative research that can inform us about our culture and identity. Autoethnography is a methodology that links the self (auto) with ethno (culture) to research (graphy). Helping students to work in this way and make these connections in their assessed work can be a challenge, but it can also help them to identify the stories that already exist inside themselves and give them the confidence to believe that these stories might matter in the world beyond their writing journals and university lectures. In this article, the authors share personal stories to reflect on our pedagogic approach to undergraduate creative writing teaching.